The Effect Of Entrepreneurial Orientation And Creativity On The Development Of Small Business Credit Union Members On The Cu Lanamona, Maliana Timor Leste - Jacinta Dos Santos; Endang Eveline Giri; Augusto da Conceição Soares (ABM: International Journal of Administration, Business and Management, 2020)
This study aims to analyze and explain; (1) The effect of entrepreneurial orientation on the development of small businesses of members of Lanamona; (2) The effect of creativity on the development of small businesses of members of Lanamona. The population in this study was 130 members of CU Lanamona engaged in small business, in the municipality of Bobonaro. Of this total collected all questionnaires distributed. The data analysis method uses SPSS. The findings of this study are that the entrepreneurial orientation variable has a positive and partially significant effect on the development of small businesses. This is evidenced by the value of t-count 2.775 greater than t-table 1.97810. These results suggest that entrepreneurial orientation is a factor that plays an important role in determining the level of improvement of small business development. The higher entrepreneurial orientation, will encourage the higher development of small businesses. Conversely, if entrepreneurship orientation is low, business development will also experience a decline. The variable of creativity has a positive and partially significant effect on the development of small businesses. Therefore, the higher the creativity that is carried out by entrepreneurs, the business development will increase. This is evidenced by the value of t-count (3.857) is greater than t-table (1.97810). Entrepreneurial orientation and creativity variables simultaneously have a positive and significant effect on the development of small businesses. This is evidenced by the calculated F-count (32,746) greater than F-table (3.07). So that it can be said that the higher or better the entrepreneurial orientation and creativity of an entrepreneur, the more business development will increase. Keywords: Entrepreneurial Orientation, Creativity, Small Business Development